Taxa de atração para equações de reação-difusão com difusão grande localizada - Pires, Leonardo (Universidade Federal de São Carlos, 2013)
In this work we study the nonlinear asymptotical dynamics of a semilinear reactiondiffusion equation of parabolic type, when the diffusion coefficient becomes very large in a subregion Ω0 which is interior to the physical domain Ω. We obtain, under suitable assumptions, that the family of attractors behave continuously with respect to a rate of attraction.
Keywords: Equações diferenciais parciais; Equações de reação e difusão (Matemática); Sistemas dinâmicos não-lineares; Atratores (Matemática); CIENCIAS EXATAS E DA TERRA::MATEMATICA